The Relationship Between Parent's Role in Learning Assistance with Children's Reading Learning Outcome at PAUD Ceria Kasih Bunda During Covid-19 Pandemic - Muhammad Yunus; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
The purpose of this study is to see whether or not there is a relevant relationship between the role of parents in children's learning activities and children's reading learning outcomes at Ceria Kasih Bunda PAUD. The type of research on this research is descriptive correlational which is then carried out through a quantitative approach. The population in this study were the female parents of Ceria Kasih Bunda PAUD children, totaling 34 people, with a sample size of 17 people and to collect data, the process of distributing questionnaires or questionnaires had finished testing its validity and reliability. The data analysis obtained was 1) the role of parents in children's learning activities obtained 25.48% who gave always answers and 47.37% who gave frequent answers, so it can be categorized quite well. 2) children's learning to read results obtained 46.62% with moderately developed answers and 15.95% with developing answers as expected, so it can be categorized that children's learning outcomes are quite good at Ceria Kasih Bunda PAUD during the covid-19 pandemic. After testing the hypothesis using the SPSS application, the results showed that there was no relevant relationship between the role of parents in children's learning activities and the results of learning to read children at Ceria Cinta Bunda during the COVID-19 pandemic because the data obtained were r_count = 0.003 and The value was consulted with r_(table ) = 0.456 with N = 16. Based on the results of the consultation, it was obtained r_hitung>r_(table). If r_table is greater than r_(count ) then H_0 is accepted and vice versa H_1 is rejected.Keywords: Education, Early Childhood Education, Learning Activities, Reading Learning Outcomes